The Pathogenesis of Atopic Dermatitis: The Role of Filaggrin - Tamarachiara Kuntjoro; Erna Harijati (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Atopic dermatitis (AD) is a multifactorial skin disease with waxing and waning inflammatory process. In recent years, genetic mutations namely the null mutations of the filaggrin gene (FLG) has been the focus in AD risk factors investigations. Purpose: To highlight the emerging topic on the role of filaggrin as an important element in the pathogenesis of AD. Reviews: Filaggrin binds to cytoskeleton keratin to bring the physical strength to corneocytes. Filaggrin will be degraded to amino acids that conserve acidic pH and condensation of the skin. Patients with FLG null mutations are more likely to experience early-onset, severe and persistent AD. AD patients with FLG R501X null mutations are reported to be the least responsive to therapy. Conclusion: A filaggrin deficit is the main culprit in AD development that eventually leads to the defective skin barriers, reduction in natural moisturizing factors (NMF), infections and inflammation. FLG mutations associates with the phenotypes and course of AD which could be examined using Raman-determined NMF.